PRIMARY HYPOTHYROIDSIS – DIAGNOSIS AT THE JOINT OF TWO SPECIALITIES - Negmatova , Gulzoda Shukhratovna; Mansurova, Gulsum Zaydinovna; Xosilova , Nilufar Maxmasodiq qizi; Abdiyev, Lazizbek Sobir oʻgʻli (Educational Research in Universal Sciences, 2024)
Hypothyroidism is a condition with an estimated prevalence in the general population of 0.3% - 3.7% in the USA and 0.2%-5.3% in Europe, depending on the definition used (1). Approximately 12% of the adult population has subclinical hypothyroidism (2, 3). The diagnosis and treatment of (subclinical) hypothyroidism has traditionally been considered rather straightforward. On closer examination, however, many unresolved issues remain and patient satisfaction in terms of symptom relief is often suboptimal (4). Several factors may contribute to this situation.